Water Supply, Sanitation, and Hygiene (WASH) and COVID-19 : Critical WASH Interventions for Effective COVID-19 Pandemic Response - World Bank (World Bank, Washington, DC, 2020)
Safely managed water supply, sanitation, and hygiene (WASH) services are an essential part of preventing disease and protecting human health during infectious disease outbreaks, including the current COVID-19 pandemic. One of the most cost-effective strategies for increasing pandemic preparedness, especially in resource-constrained settings, consists of investing to strengthen core public health infrastructure, including water supply and sanitation systems. Good and consistently applied WASH and waste management practices serve as essential barriers to human-to-human transmission of the COVID-19 virus in communities, homes, health care facilities, schools, and other public spaces.